Ophthalmic Graves' disease in monozygotic twins. Issue 607 (May 1976) - Thornham, J. R.; Nutt, J. E.; Clark, F.
Abstract : A pair of identical female twins with ophthalmic Graves' disease is described. Monozygosity was confirmed by analysis of blood groups and red cell isoenzymes. Thyroid status was assessed by standard tests (serum thyroxine (Thyopac-4), protein-bound iodine, Thyopac-3 and thyroid uptake of 131 I). In addition, serum triiodothyronine and the response in thyroid stimulating hormone to thyrotrophin releasing hormone was measured. Circulating autoantibodies to thyroid tissue were detected in both sisters by complement fixation and immunofluorescence methods but long acting thyroid stimulator was not found.